2015
DOI: 10.3109/0284186x.2014.990158
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of regular aspirin use on overall and cancer-specific survival in patients with colorectal cancer harboring a PIK3CA mutation

Abstract: Background Recent data have suggested that regular aspirin use improves overall and cancer-specific survival in the subset of colorectal cancer (CRC) patients harboring PIK3CA mutations. However, the number of PIK3CA-mutated CRC patients examined in these studies was modest. Our collaborative study aims to validate the association between regular aspirin use and survival in patients with PIK3CA-mutated CRC. Patients and methods Patients with PIK3CA-mutated CRC were identified at Moffitt Cancer Center (MCC) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…In line with our finding recent data have suggested that regular aspirin use improves overall and cancer-specific survival in the subset of colorectal cancer (CRC) patients [7]. Aspirin is also a promising chemopreventive agent and exerts significant therapeutic potentials in pancreatic cancer [8].…”
Section: Discussionsupporting
confidence: 78%
“…In line with our finding recent data have suggested that regular aspirin use improves overall and cancer-specific survival in the subset of colorectal cancer (CRC) patients [7]. Aspirin is also a promising chemopreventive agent and exerts significant therapeutic potentials in pancreatic cancer [8].…”
Section: Discussionsupporting
confidence: 78%
“…Domingo et al 81 and Liao et al 82 found a survival advantage for posttreatment aspirin users only in patients whose tumors exhibit PIK3CA mutations; however, a recent cohort study did not validate these observations. 83 Multiple prospective studies are under way to address the potential benefit of adding aspirin or other nonsteroidal anti-inflammatory drugs to adjuvant therapy. This recommendation is supported by two systematic reviews 33,40 obtained from our systematic review.…”
mentioning
confidence: 99%
“…This is highlighted in a study by Kothari and colleagues, who combined data from two large academic institutions and examined the association between regular aspirin use and improved survival in PIK3CA-mutated CRC patients. The authors found that regular aspirin use was not associated with improved OS (multivariate HR 0.96; p = 0.86) and despite a trend towards improved cancer-specific survival (multivariate HR 0.60; p = 0.14), this was not significant [179]. As a result, mutations in PIK3CA may serve as a predictive biomarker for adjuvant aspirin therapy, however, further investigations involving prospective randomized studies are warranted.…”
Section: Pik3ca Mutations and Adjuvant Aspirinmentioning
confidence: 93%
“…In their prospective two cohort studies, coexistence of PIK3CA exon 9 and 20 mutations but not in either exon alone, was associated with significantly worse cancer-specific survival (log-rank p = 0.0008; multivariate HR = 3.51; 95% CI, 1.28-9.62] and OS (log-rank p = 0.0008; multivariate HR = 2.68; 95% CI, 1.24-5.77) [80] (Table 2). On the contrary, other studies suggest that mutant PIK3CA may not be as predictive as first thought [179]. This is highlighted in a study by Kothari and colleagues, who combined data from two large academic institutions and examined the association between regular aspirin use and improved survival in PIK3CA-mutated CRC patients.…”
Section: Pik3ca Mutations and Adjuvant Aspirinmentioning
confidence: 98%